Focus group discussion (FGD) on a school-based intervention program to combat obesity in Malaysian schools - Ishak, Z.; Low, S.F. (2015)

(untitled)
The objective of this report is to present a Focus Group Discussion (FGD) that seeks to formulate recommendations to improve on a school-based intervention programme to combat obesity in Malaysia schools. The intervention program is made up of three components, namely Small Sided Game (SSG), Psychology and Nutrition. The FGD is carried out after 6 months intervention in three different groups consist of teachers, primary students and secondary students. For each session 7-10 participants will be selected randomly representing the groups. The discussion demonstrates that co-curriculum activities in the school, teachers, parents, peers, facilitators who conduct the activities and participants' determination in losing weight play a vital role during the intervention. In general, the aspect that affects the involvement of teachers is time consuming during the intervention programme. Teachers are burdened with teaching work load but in contracts the students are happy with the SSG components and they believe that the intervention can reduce their weight. For the psychology component the students prefer to have more outside classroom activities and for nutrition more on hand-on activities. The findings have provided significant outputs to the Ministry of Health and Ministry of Education in helping obese children to live healthier and achieve well-being in their diary life. However,the intervention programme to combat obesity will be sustainable at school if extra human resources who are well-trained with three component of the programme are placed at schools.